Synergistic Promotion of Direct Interspecies Electron Transfer by Biochar and Fe₃O₄ Nanoparticles to Enhance Methanogenesis in Anaerobic Digestion of Vegetable Waste - Hongruo Ma; Long Chen; Wei Guo; Lei Wang; Jian Zhang; Dongting Zhang (Fermentation)
When vegetable waste (VW) is used as a sole substrate for anaerobic digestion (AD), the rapid accumulation of volatile fatty acids (VFAs) can impede interspecies electron transfer (IET), resulting in a relatively low biogas production rate. In this study, Chinese cabbage and cabbage were selected as the VW substrates, and four continuous stirred tank reactors (CSTRs) were employed. Different concentrations of biochar-loaded nano-Fe3O4(Fe3O4@BC) (100 mg/L, 200 mg/L, 300 mg/L) were added, and the organic loading rate (OLR) was gradually increased during the AD process. The changes in biogas production rate, VFAs, and microbial community structure in the fermentation tanks were analyzed to identify the optimal dosage of Fe3O4@BC and the maximum OLR. The results indicated that at the maximum OLR of 3.715 g (VS)/L·d, the addition of 200 mg/L of Fe3O4@BC most effectively promoted an increase in the biogas production rate and reduced the accumulation of VFAs compared to the other treatments. Under these conditions, the biogas production rate reached 0.658 L/g (VS). Furthermore, the addition of Fe3O4@BC enhanced both the diversity and abundance of bacteria and archaea. At the genus level, the abundance of Christensenellaceae_R-7_group, Sphaerochaeta, and the archaeal genus Thermovirga was notably increased.